PENGARUH ETNOSENTRISME DAN KONTAK ANTAR BUDAYA TERHADAP SIKAP NASIONALISME PADA MAHASISWA FISIP UNEJ ANGKATAN 2023, 2024, DAN 2025 - Yulio Muhammad Arifin; Ratna Endang Widuatie; Ali Reza; Insanun Qomariyah; Zahrotul Khoirunnisa; Fahmil Ali (PT. Hasba Edukasi Mandiri, 2025)
Explanatory quantitative research examining the influence of ethnocentrism and cross-cultural interaction on nationalism attitudes among students of the Faculty of Social and Political Sciences, University of Jember, class of 2023 to 2025. Multiple linear regression analysis yielded a surprising result: ethnocentrism had no significant effect on nationalism (t=-0.641; sig=0.525). This finding indicates that a tendency to view one's own culture as superior does not automatically strengthen or weaken national pride. Conversely, intercultural contact proved to have a positive and highly significant influence (t=7.068; sig=0.000). This suggests that constructive interaction with different cultural groups actually strengthens national spirit. The simultaneous test (F=30.904; sig=0.000) confirms that both variables jointly influence nationalism, with a coefficient of determination of 56.8%, indicating that over half the variation in nationalism is explained by these independent variables. The key finding asserts that the more intensive and qualitative the students' cross-cultural interactions, the stronger their nationalist attitude. The implication is clear: educational institutions are encouraged to systematically strengthen national character-building programs based on intercultural interaction, through student exchanges, inclusive courses, and inclusive student activities. This approach is proven more effective in fostering an inclusive and contextual nationalism compared to a closed and exclusive approach. Therefore, nurturing love for one's homeland in this globalization era can be achieved by opening windows to cultural diversity, not by closing oneself off from it.